2016
DOI: 10.1007/s00228-016-2159-1
|View full text |Cite
|
Sign up to set email alerts
|

Improved participants’ understanding of research information in real settings using the SIDCER informed consent form: a randomized-controlled informed consent study nested with eight clinical trials

Abstract: Improved participants' understanding of research information in real settings using the SIDCER informed consent form: a randomized-controlled informed consent study nested with eight clinical trials SIDCER インフォームドコンセント書式を用いた研究参加者の内容理解改善:8 件の臨床試験 を用いたインフォームドコンセントのランダム化比較試験

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 28 publications
1
8
1
Order By: Relevance
“…The SIDCER ICF was found to be superior to the conventional ICF in improving parental understanding of several elements of the ICF content. The overall results of this study are consistent with three previous informed consent studies that exhibited the improvement of participants’ understanding by the SIDCER ICF 17 19 20. In line with a recent integrative review on informed consent, it is reasonable to assume that the evidence of improved participants’ understanding by the SIDCER ICF is largely attributable to its simplicity and concise format with increased processability (using summary boxes, highlights and illustrations, when appropriate) 23…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The SIDCER ICF was found to be superior to the conventional ICF in improving parental understanding of several elements of the ICF content. The overall results of this study are consistent with three previous informed consent studies that exhibited the improvement of participants’ understanding by the SIDCER ICF 17 19 20. In line with a recent integrative review on informed consent, it is reasonable to assume that the evidence of improved participants’ understanding by the SIDCER ICF is largely attributable to its simplicity and concise format with increased processability (using summary boxes, highlights and illustrations, when appropriate) 23…”
Section: Discussionsupporting
confidence: 88%
“…Parental understanding of essential research-related information was measured using the questionnaire (in Thai), which was modified from our previous studies 17 19 20. It consisted of 24 scenario-based questions which assessed parental understanding of relevant ICF content in the following categories: general items (five questions), patient’s rights (four questions), scientific aspects (eight questions) and ethics aspects (seven questions).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding supports the current dogma in the field that individuals with higher levels of education have a better understanding of the consent information compared with those with lower levels of education 24 25. Furthermore, it has been shown that the SIDCER ICF was particularly effective among participants whose education was at the high school level or below, but it had little effect on those who had a bachelor degree or above (see figure 2 and Koonrungsesomboon  et al 14). This indicates the value of the SIDCER ICF in clinical research involving participants with low levels of education who are commonly found to have a limited understanding of information in ICFs 24 25…”
Section: Discussionmentioning
confidence: 99%
“…The use of visual aids, multiple-choice examinations, videotapes, and multimedia adjuncts to improve recall have been reported, with conflicting results (9)(10)(11)(12)(13). Using a personalized letter in simple language, we were able to significantly improve patients' recall.…”
Section: Discussionmentioning
confidence: 89%